The implications of different lateral wall thicknesses on surgical access to the maxillary sinus - Ee Lian Lim; Wei Cheong Ngeow; Daniel Lim (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract: The objective of this study was to measure the topographic thickness of the lateral wall of the maxillary sinus in selected Asian populations. Measurements were made on the lateral walls of maxillary sinuses recorded using CBCT in a convenient sample of patients attending an Asian teaching hospital. The points of measurement were the intersections between the axes along the apices of the canine, first premolar, and second premolar and along the mesiobuccal and distobuccal apices of the first and second molars and horizontal planes 10 mm, 20 mm, 30 mm and 40 mm beneath the orbital floor. The CBCT images of 109 patients were reviewed. The mean age of the patients was 33.0 (SD 14.8) years. Almost three quarters (71.8%) of the patients were male. The mean bone thickness decreased beginning at the 10-mm level and continuing to 40 mm below the orbital floor. Few canine regions showed encroachment of the maxillary sinus. The thickness of the buccal wall gradually increased from the canine region (where sinus encroachment of the canine region was present) to the first molar region, after which it decreased to the thickness observed at the canine region. The buccal wall of the maxillary sinus became thicker anteroposteriorly, except in the region of the second molar, and thinner superoinferiorly. These changes will affect the approach used to osteotomize the lateral sinus wall for oral surgery and for the sinus lift procedure.